НОВІТНІ КОМП'ЮТЕРНІ ТЕХНОЛОГІЇ - НА ДОПОМОГУ МАЙБУТНІМ ВИКЛАДАЧАМ МУЗИКИ (Педагогіка вищої та середньої школи, 2007)
The article discusses the need and some questions about arranging music in ways computer technologies by future music teachers.